Socialization of New Normal Implementation at Al-Jabbar Islamic High School in 2021 - Febi Ratnasari; Zahrah Maulidia Septimar (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The current pandemic condition requires everyone to be prepared to deal with it, as well as school children. Students must be equipped with knowledge about the application of the new normal at school, the purpose of this activity is that high school students (SMA) can behave and behave in accordance with health protocols in the new normal era so that students can avoid the spread or exposure of the novel coronavirus (covid-19). 19) during face-to-face school. The knowledge gained by students is done by providing health education. Health education is provided by the online method, using the ZOOM meeting application, with the participants of the webinar being students of Al-Jabbar Islamic High School, Tangerang City. The results of the Health Education activity obtained positive attitudes of students before being given Health Education by 50% (15 students), and after being given 66.67% (20 students), while the behavior of implementing the new normal according to the health protocol before health education was carried out by 53.33% (16 students), whereas after being given health education it was 80% (24 students).